(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Numerical simulation performed in this paper to explore the flexural behavior of RC one way slab strengthened with fiber reinforcement cementations matrix (FRCM). Three dimensional finite element analysis was performed by using ANSYS (17.2). The main issues focused in this paper are (1) the effect of FRCM fabric types on the flexural behavior of strengthened RC slab in terms of both ultimate capacity and deflection, (2) effect of variables compressive strength value of the concrete slab and (3) number of fabric layers for composite material effect. The results showed that the fabric type had a clear effect on the flexural behavior of the strengthened slab. The parametric study also revealed that the flexural strength increases with increasing the compressive strength of concrete when the failure is represented by crushing of the concrete strut. In addition to, the number of fabric layers for composite material had a clear effect on the behavior of RC slab, but to a specified number because then the failure is determined by the action of the concrete in the compression zone.